Hypertension-Linked Mutation of α-Adducin Increases CFTR Surface Expression and Activity in HEK and Cultured Rat Distal Convoluted Tubule Cells - Mondini, Anna; Sassone, Francesca; Civello, Davide Antonio; Garavaglia, Maria Lisa; Bazzini, Claudia; Rodighiero, Simona; Vezzoli, Valeria; Conti, Fabio; Torielli, Lucia; Capasso, Giovanbattista; Paulmichl, Markus; Meyer, Giuliano (PloS one, 2012)
The CFTR (Cystic Fibrosis Transmembrane Conductance Regulator) activity and localization are influenced by the cytoskeleton, in particular by actin and its polymerization state. In this study we investigated whether the expression of the hypertensive mutations of α-adducin (G460W-S586C in humans, F316Y in rats), an actin capping protein, led to a functional modification of CFTR activity and surface expression. The experiments were performed on HEK293 T cells cotransfected with CFTR and the human wild type (WT) or G460W mutated α-adducin. In whole-cell patch-clamp experiments, both the CFTR chloride current and the slope of current activation after forskolin addition were significantly higher in HEK cells overexpressing the G460W adducin. A higher plasma membrane density of active CFTR channels was confirmed by cell-attached patch-clamp experiments, both in HEK cells and in cultured primary DCT cells, isolated from MHS (Milan Hypertensive Strain, a Wistar rat (Rattus norvegicus) hypertensive model carrying the F316Y adducin mutation), compared to MNS (Milan Normotensive Strain) rats. Western blot experiments demonstrated an increase of the plasma membrane CFTR protein expression, with a modification of the channel glycosylation state, in the presence of the mutated adducin. A higher retention of CFTR protein in the plasma membrane was confirmed both by FRAP (Fluorescence Recovery After Photobleaching) and photoactivation experiments. The present data indicate that in HEK cells and in isolated DCT cells the presence of the G460W-S586C hypertensive variant of adducin increases CFTR channel activity, possibly by altering its membrane turnover and inducing a retention of the channel in the plasmamembrane. Since CFTR is known to modulate the activity of many others transport systems, the increased surface expression of the channel could have consequences on the whole network of transport in kidney cells.